PENGARUH PENGEMBANGAN KARIER DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KECAMATAN CILEDUG KOTA TANGERANG - Hanifa Pratama Putri; Lili Sularmi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of career development and work environment on employee performance at the Ciledug District Office, Tangerang City. The background of this research arises from the limited implementation of career development programs and the less optimal work environment, which are suspected to influence employee performance. This study uses a quantitative approach with an associative method. The sample in this study consisted of 86 employees of Ciledug District.. The data collection technique was carried out through questionnaires using a Likert scale, while the data analysis was processed with SPSS version 26, including validity test, reliability test, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results show that the career development variable (X1) has a positive and significant effect on employee performance, with a t value of 7.862 > t table 1.989 and a significance value of 0.000 < 0.05. The work environment variable (X2) also has a positive and significant effect on employee performance, with a t value of 6.472 > t table 1.989 and a significance value of 0.000 < 0.05. Simultaneously, both variables significantly affect employee performance, with an F value of 35.487 > F table 3.110 and a significance value of 0.000 < 0.05. The coefficient of determination of 46.1% indicates that career development and work environment contribute to improving employee performance, while the remaining 53.9% is influenced by other factors. The results emphasize the importance of continuous career development and a conducive work environment in enhancing employee performance at the Ciledug District Office, Tangerang City.